Impacts of elevated carbon dioxide on carbon gains and losses from soil and associated microbes in a Eucalyptus woodland. (April 2020) - Castañeda-Gómez, Laura; Walker, Jennifer K.M.; Powell, Jeff R.; Ellsworth, David S.; Pendall, Elise; Carrillo, Yolima
Abstract: Increased soil carbon (C) gains projected to occur with elevated CO2 (eCO2 ) might be negated by higher C losses via soil organic matter (SOM) decomposition. The impact of eCO2 on soil C is usually measured as a change in total soil C which inevitably confounds C gains and losses occurring simultaneously. Furthermore, the impacts of eCO2 on C gains and losses may differ for contrasting soil organic substrates due to their distinctive physicochemical and microbiological characteristics. Projecting the impacts of eCO2 on soil C greatly depends on quantifying its individual effects on C gains and losses, which is rarely done in field settings. We used a novel combination of litter bag and isotopic approaches to study temporal C dynamics in two organic substrates: root litter and mineral soil C (SOM-C) to assess C dynamics in a mature Eucalyptus woodland under CO2 enrichment (EucFACE). We aimed to isotopically separate different C pools for both substrates: a new C pool (Cnew, plant-derived C from the study site) and a pre-existent, old C pool (Cold, present in the original substrates). We also performed comprehensive microbial community analyses to investigate relationships between microbial community structure and individual C pools. We found higher root litter mass losses and slightly greater SOM-C Cold losses with eCO2 during summer months. Gains of Cnew were not affected by eCO2, except for SOM-C during summer, which is linked with the observed Cold losses from SOM-C. Moreover, fungal abundance in root litter increased with eCO2 but decreased in SOM-C. Temporal changes rather than eCO2 -induced changes in microbial communities were related to C dynamics. Taken together our results suggest that eCO2 did not lead to significant Cnew gains but instead lead to moderate enhancement of Cnew and Cold losses, suggesting limited capacity for increased C sequestration of this mature woodland. Graphical abstract: Image 1 Highlights: We quantified the simultaneous impact of elevated CO2 on soil C gains and losses. Elevated CO2 elicits substrate-dependent and seasonal increases in C losses. Higher C losses were paired with seasonal increases in plant-derived C gains. Impacts of elevated CO2 on the microbial community are substrate-dependent. Temporal shifts in microbial communities were linked with altered C dynamics.